Sosyal Koruma Açısından İslâm’da Yoksul ve Miskinlerin Yeri - Yumurtacı, Aynur (FSM Vakıf Üniversitesi)
Yoksulluk geçmişten günümüze pek çok araştırmacının üzerinde önemle durduğu bir konu olmuştur. Ancak yoksulluk genellikle tek boyut üzerinden düşünülmüş ve yoksulluğu önleme amaçlı üretilen politikalar da tek boyutlu olmuştur. Oysa yoksulluğun farklı ve özel anlam içeren bir boyutu da bulunmaktadır. Bu boyut miskinliktir. Miskinlerin, yoksulluğun görünmeyen bir yüzü olduğunu bilmek ve sosyal koruma kapsamına nasıl alınacağını tespit etmek sosyal dengelerin sağlanması bakımından önemlidir. Bu çalışmada İslâm’ın korunmasını emrettiği özel gruplardan biri olan gizli yoksullara (miskinlere) yönelik sosyal korumanın nasıl ve hangi araçlarla sağlanabileceği sorularına yanıt aranmaktadır. Bu arayışta sahip olduğu mükemmel potansiyel ile zekât müessesesinin önemi vurgulanmaktadır.

Poverty has been a topic that was strongly focussed by many researchers from past to present. However, poverty has usually been thought out at one dimension and policies, produced for aiming to prevent poverty, have also been one-dimensional. But, there is also a dimension that contains different and special meaning of poverty. This dimension is the unseen-poor. To know the unseen poor as being an invisible face of poverty and how to detect them into social protection is important in terms of providing social balances. In this study, looking for answers to the questions about how and which tools provide to social protection for unseen poor as a particular group that ordered the protection of Islam. The importance of Alms (Zekat) institutions that have excellent potential in this quest are highlighted.
The Place of Poor and Unseen Poor in Islam in Terms of Social Protection
Keywords: İslâm; Miskin; Yoksul; Sosyal koruma; Sosyal yardım; Islam; Unseen/silent poor; Poor; Social protection; Social assistance